The attribution problem with information security attacks. Issue 5 (May 2017) - Farral, Travis
Abstract : Russia's supposed involvement in the US election has been at the top of the news agenda for a while now. Yet despite this elevated attention, questions surrounding the association remain unanswered. What did the Russians do and why? Can we definitively name Russia as the perpetrator? The troubling concept of attribution stands in the way of conclusive answers. It remains a highly debated and often controversial topic within information security circles, as attributing attacks to specific adversaries has become more of an educated guess than strong, court-ready evidence.